Pengembangan Bahan Ajar Tematik Berbasis Kearifan Lokal Bima Tema 8 Subtema 2 Untuk Kelas IV SDN INPRES RATO Tahun Pelajaran 2020/2021 - Arif Alam; Nurul Kemala Dewi; Heri Setiawan (Pendagogia: Jurnal Pendidikan Dasar, 2021)
The purpose of this research is to develop thematic teaching materials based on local wisdom of Bima. The theme of the area where I live, the sub-theme of the uniqueness of the area where I live in grade IV SDN INPRES RATO and to determine the feasibility of thematic teaching materials based on Bima's local wisdom. SDN INPRES RATO. This research method is R&D (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The population in this study were all fourth grade students of SDN SDN INPRES RATO. While the sample in this study were 20 students because this study used a small group. The results of this study are design expert validators get a percentage of 94% in the very feasible category, material expert validators get a percentage of 98% in the very feasible category, learning expert validators get a percentage of 94% in the very feasible category. Very feasible category, student responses got a percentage of 96% in the very category. worth itThe purpose of this research is to develop thematic teaching materials based on local wisdom of Bima. The theme of the area where I live, the sub-theme of the uniqueness of the area where I live in grade IV SDN INPRES RATO and to determine the feasibility of thematic teaching materials based on Bima's local wisdom. SDN INPRES RATO. This research method is R&D (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The population in this study were all fourth grade students of SDN SDN INPRES RATO. While the sample in this study were 20 students because this study used a small group. The results of this study are design expert validators get a percentage of 94% in the very feasible category, material expert validators get a percentage of 98% in the very feasible category, learning expert validators get a percentage of 94% in the very feasible category. Very feasible category, student responses got a percentage of 96% in the very category. worth it